Two-state Bose-Hubbard model in the hard-core boson limit - Stasyuk, I.V.; Velychko, O.V. (Condensed Matter Physics, 2011)
Phase transition into the phase with Bose-Einstein (BE) condensate in the two-band Bose-Hubbard model with the particle hopping in the excited band only is investigated. Instability connected with such a transition (which appears at excitation energies δ <|t′₍₎|, where |t′₍₎| is the particle hopping parameter) is considered. The reentrant behaviour of spinodales is revealed in the hard-core boson limit in the region of positive valuesof chemical potential. It is found that the order of the phase transition undergoes a change in this case and becomes the first one; the re-entrant transition into the normal phase does not take place in reality. First order phase transitions also exist at negative values of δ (under the conditionδ > δcrit ≈ −0.12|t′₍₎|). At μ <0the phase transition mostly remains to be of the second order. The behaviour of the BE-condensate order parameter is analyzed, the (Θ, μ) and(|t′₍₎|, μ) phase diagrams are built and localizations of tricritical points are established. The conditions are found at which the separation on the normal phase and the phase with the BE condensate takes place. Дослiджено перехiд у фазу з бозе-конденсатом у двозоннiй моделi Бозе-Хаббарда з переносом частинок лише у збудженiй зонi. Розглянуто нестiйкiсть, пов’язану з таким переходом, який вiдбувається при енергiях збудження δ <|t′0| (де |t′0| – параметр перескоку частинок). У границi жорстких бозонiв виявлено зворотнiй хiд спiнодалей в областi додатних значень хiмiчного потенцiалу. Встановлено, що рiд фазового переходу у цьому випадку змiнюється на перший i повернення до нормальної фази насправдi не вiдбувається. Переходи першого роду iснують i при вiд’ємнiй енергiї δ(за умови δ > δ crit ≈ −0.12|t′0|). При μ<0 фазовий перехiд залишається переважно переходом другого роду. Проаналiзовано хiд параметра порядку бозе-конденсату, побудовано фазовi (Θ,μ) i (|t′0|, μ) дiаграми, встановлено локалiзацiю трикритичних точок. Знайдено умови, при яких для фiксованої концентрацiї частинок наступає розшарування на нормальну фазу i фазу з бозе-конденсатом.